Cerebral and extracerebral vasoreactivity in symptomatic lacunar stroke patients: a case‐control study. Issue 6 (15th February 2012) - Deplanque, Dominique; Lavallee, Philippa C.; Labreuche, Julien; Gongora‐Rivera, Fernando; Jaramillo, Arturo; Brenner, David; Abboud, Halim; Klein, Isabelle F.; Touboul, Pierre‐Jean; Vicaut, Eric; Amarenco, Pierre; ,
Abstract : Background: Whether cerebral artery endothelial dysfunction is a key factor of symptomatic lacunar stroke and cerebral small vessel disease remains unclear. Methods: Cerebral and extracerebral vasoreactivity were measured in 81 patients with recent symptomatic lacunar stroke and in 81 control subjects matched for main vascular risk factors. Cerebral vasoreactivity and carotid endothelial‐dependent vasodilation were measured after five‐minutes of carbon dioxide‐induced hypercapnia. Brachial endothelial‐dependent vasodilation was assessed after hyperemia induced by deflating a cuff around the forearm previously inflated to 200 mmHg for four‐minutes. Carotid and brachial endothelial‐independent vasodilation were measured five‐minutes after administration of sublingual nitroglycerin 300 μg. Brain magnetic resonance imaging were analyzed in lacunar stroke patients. Results: One‐month after stroke onset, patients had more severely impaired cerebral vasoreactivitys than matched controls (mean ± standard deviation, 14·4 ± 12·1% vs. 19·4 ± 17·4%; P = 0·049). Severe alterations of both carotid and brachial endothelial‐dependent and at a lesser degree of carotid and brachial endothelial‐independent vasodilation were observed in both groups. After adjustment for confounders, subjects with a cerebral vasoreactivity value in the two lower tertiles (≤19·6%) were more likely to have had a symptomatic lacunar stroke (adjusted odds ratio, 3·78; 95% confidence interval, 1·42 to 10·08; P = 0·008). Only alteration of brachial endothelial‐independent vasodilation correlated with parenchymal abnormalities, namely microbleeds and leukoaraiosis. Conclusions: While abnormalities in extracerebral vasoreactivity seem related to vascular risk factors, the severity of endothelial dysfunction in cerebral arteries may be determinant in the occurrence of symptomatic lacunar stroke in patients with small vessel disease.